2014
DOI: 10.1007/s00784-014-1268-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical results of implant placement in resorbed ridges using simultaneous guided bone regeneration: a multicenter case series

Abstract: The handling characteristics of CPS putty may simplify GBR protocol. Implants placed in conjunction with GBR have a very good survival rate after 1 year of follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 17 publications
3
42
0
Order By: Relevance
“…However, only a few of these studies [2527] reported on alveolar ridge reconstruction with titanium meshes and simultaneous implant placement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, only a few of these studies [2527] reported on alveolar ridge reconstruction with titanium meshes and simultaneous implant placement.…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies have demonstrated that titanium meshes can promote the formation of new bone, when positioned before [19–24] or simultaneously with dental implants [2527]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,25 During the first year after loading, reportedly highly acceptable levels of marginal bone loss were observed on radiographs: 0.50 6 0.26 mm on the mesial side and 0.58 6 0.23 mm on the distal side of implants. 22,26-28 Bone loss can occur after loading, due to maturation and adaptation of the marginal bone.…”
Section: Discussionmentioning
confidence: 96%
“…The mean defect height coverage observed in this study (79%) lies within the range of those reported in several clinical GBR studies (75%-81%). 5,6 Although there is considerable evidence for the survival of implants placed in conjunction with GBR, the long-term stability of regenerated buccal bones may differ from that survival rate. 7 It has been shown in clinical studies that a predictable result with GBR requires certain conditions, such as wound stabilization, and space creation and maintenance.…”
Section: Discussionmentioning
confidence: 99%